Undesirable Microbial Growth from The Biodegradation Process of Nypa Palm Fronds Suplemented with Cellulolytic Bacteria Culture Isolated from Nypa Palm Worms (Namalycastis rhodochorde) - Williem, Albertus; Kurniatuhadi, Rikhsan; Setyawati, Tri Rima; Yanti, Ari Hepi (Jurnal Biologi Tropis, 2024)
Biodegradation of nipa palm fronds using cellulolytic bacteria on an in-vitro scale was conducted to produce feed for cultivating palm worms (Namalycastis rhodochorde). The spontaneous degradation process is thought to trigger the growth of other microbes from raw materials from unsterilized nypa palm fronds. This research aims to determine the presence of different microbes that participate in the degradation process of palm fronds supplemented with cellulolytic bacterial isolates. The biodegradation process was conducted using dry palm fronds that were not sterilized, without pressurized heat, for 30 days in a sterile container. Cellulolytic bacterial isolates were added to facilitate the process. The research results revealed three characteristics of bacterial colonies with two cell shapes: bacilli and spirals bacterial isolates. The study also identified the presence of protozoa that exhibited morphological similarities to the Ciliophora group. This research provides valuable reports for further studies on the biodegradation process of palm fronds, specifically about ensuring feed safety for cultivating nypa palm worms.